Effect of Azofert®-F on the stomatal response of beans to water deficit - Estrada-Prado, Wilfredo (2021)
Introduction. Water deficit is the abiotic stress with the highest incidence on the growth and yield of bean plants. For this reason, alternatives are being sought to mitigate its adverse effects, such as the use of biofertilizers based on the microbial biodiversity existing in the soil. Objective. The effect of Azofert¨-F inoculant on the stomatal index (IE) of bean plants was evaluated under water stress conditions. Materials and methods. The experiment was carried out in the period 2016-2017 in a room with fluorescent lamps of the Department of Plant Physiology and Biochemistry of the National Institute of Agricultural Sciences, San José de las Lajas, Mayabeque, Cuba. For the anatomical study, the leaf epidermis was observed with an optical light microscope (Motic) and photographed with a coupled camera. Stomatal variables were measured using the ImageJ morphometric program and processed with the SPSS Version 22.0 statistical package. A completely randomized design was used. Ten plants were randomly selected for each treatment to evaluate density and stomatal index. Results. Azofert¨-F increased the IE of the studied cultivars. The structure of the epidermal cells was altered in both leaf surfaces when the humidity in the soil decreased; the stomatal density was modified with the presence of the product. On the abaxial surface, the occlusive cells were narrower, which showed that the leaves with the highest IE had smaller stomata. The Azofert¨-F caused the stomata to remain semi-closed when there was a water deficiency in the plants, because these bacteria helped to alleviate the water deficit by producing hormones and other enzymes that regulate the loss of water through transpiration. Conclusion. The application of Azofert¨-F increased the density and stomatal index of bean plants under conditions of water stress.